Pluralisme Agama Pada Masa Dinasti Turki Usmani dan Relevansinya dengan Kejayaan Islam - Nurkholijah Siregar (Hikmah, 2015)
The Ottoman Empire was an Islamic state berdidri success during a period of 6 centuries. There is glory in this dynasty, related to religious pluralism, makes Islam more known to the world. Sultan allows each religion to conduct activities without any fear or danger of their rights in full in Ottoman territory, because they are in a union that is under the leadership and laws of the State Ottoman.